Wandering spleen: Case report and literature review (Indian Journal of Case Reports, 2018)
The spleen is fixed in the left upper abdominal quadrant by various ligaments. Any ligament laxity or defect will result in a rare condition called “wandering spleen.” <500 cases have been reported in the literature. This study presents the case of 22-year-old female who was presented with nonspecific chronic abdominal pain and distention although; she had normal abdominal examination and laboratory investigations. A computed tomography scan showed a homogenous pelvic mass, suggesting a wandering spleen; therefore, a laparoscopic splenectomy was performed. The objective of this study was to report and review a rare condition that requires a high index of suspicion to make a correct diagnosis.